Development of Interactive Multimedia Based on Powerpoint in Science Learning in Elementary School - Sania Putriana; Nellitawati Nellitawati; Alwen Bentri; Nur Azmi Alwi (STAI Hubbulwathan Duri, 2022)
This study discusses the development of interactive multimedia learning media based on PowerPoint software in science learning in elementary schools. This study aims to produce interactive multimedia media, especially in science learning in elementary schools that are valid, practical, and effective. The type of research used is Research and Development (RnD). That is the development of interactive multimedia based on PowerPoint software in science learning. The development model used is the ADDIE model (Analyze, Design, Development, Implementation, and evaluation). The output of interactive multimedia based on PowerPoint Software is in the form of files that can be installed easily, making it easier for students in the learning process. Based on the research results, this interactive multimedia is valid, practical, and effective.